Pengaruh Locus Of Control dan Dukungan Orang Tua Terhadap Kualitas Lulusan Universitas Serelo Lahat - Yussi Rapareni; Delvina Yulanda; Rosananda Oktala (Universitas 45 Surabaya, 2024)
This research was conducted on graduates of Serelo Lahat University post-covid'19 from 2020 to 2022. The aim was to determine the Influence of Locus of Control and Parental Support individually on the Quality of Serelo Lahat University graduates, and to determine the Influence of Locus of Control and Parental Support together on the Quality of Serelo Lahat University graduates. The research design employed was Associative/Quantitative. From the results of hypothesis testing, it was found that the Locus of Control variable (X₁) had a significant value of 0.000 < 0.05, indicating a positive and significant influence on Graduate Quality. However, the Parental Support variable (X₂) had a non-significant value of 0.845 > 0.05, indicating no positive and significant influence on Graduate Quality. Furthermore, the results of hypothesis testing showed that both Locus of Control (X₁) and Parental Support (X₂) together had a significant value of 0.000 < 0.05, indicating that they jointly significantly influence Graduate Quality (Y).